2022-RA-835-ESGO AGO-OVAR 2.34/MIROVA: A randomized phase II trial of Mirvetuximab soravtansine (IMGN853), in folate receptor alpha (FRα) high recurrent ovarian cancer eligible for platinum-based chemotherapy. (20th October 2022) - Trillsch, Fabian; Schochter, Fabienne; Park-Simon, Tjoung-Won; Reuß, Alexander; Fehm, Tanja; Wimberger, Pauline; Bronger, Holger; Schmalfeldt, Barbara; Sehouli, Jalid; Marmé, Frederik; Heitz, Florian; Mahner, Sven; et al.
Abstract : Introduction/Background: Following implementation of targeted therapies to first-line treatment, repeated use of bevacizumab and/or PARPi is often not approved nor has been conclusively proven efficacious for all patients with recurrent ovarian cancer. Accordingly, new combination partners for platinum-based chemotherapy become crucial to improve outcome. For the antibody-drug conjugate, Mirvetuximab soravtansine (MIRV), containing a folate receptor alpha(FRα)-binding antibody, patients with high FRα expression according to PS2+ Scoring (cut-off: ≥75% of tumor cells with FRα membrane staining and ≥2+ intensity) had significant progression-free survival (PFS) improvements (hazard ratio: 0.55) compared to mono-chemotherapy (median PFS 5.6 vs 3.2 months, P=0.015) in the phase III FORWARD I trial. Preliminary data for combination of MIRV with carboplatin from the Phase Ib FORWARD II trial, an ORR of 71% in 17 patients with a median PFS of 15 months, and ORR of 80% in the FRα medium/high (>50% PS2+) subset of 10 patients was noted. MIRV is well-tolerated with a manageable safety profile. Methodology: Eligible patients for this multicenter, randomized, two-arm, open-label, comparative phase II trial have recurrent, FRα high epithelial cancer of the ovary, fallopian tube or peritoneum and measurable disease. Patients are eligible for platinum-based chemotherapy, had at least one prior chemotherapy, but are not candidates to receive bevacizumab. Patients with wildtype BRCA1/2 mutation status and patients with a deleterious mutation and prior PARPi therapy can be included. Following pre-screening for high FRα expression, 136 patients are randomized (1:1) to a) experimental arm: Carboplatin + MIRV 6 mg/kg IV d1 (6 cycles q21d) followed by MIRV monotherapy until disease progression or b) control arm: Platinum-based chemotherapy (6 cycles) followed by PARPi or standard of care. The primary endpoint PFS will be assessed by modified RECIST 1.1. Key secondary endpoints include overall survival, ORR, and quality of life. NCT04274426 Results: Enrolment started. Conclusion: Trial in Progress.